If it's not what You are looking for type in the equation solver your own equation and let us solve it.
p-6/14=-1
We move all terms to the left:
p-6/14-(-1)=0
We add all the numbers together, and all the variables
p+1-6/14=0
We multiply all the terms by the denominator
p*14-6+1*14=0
We add all the numbers together, and all the variables
p*14+8=0
Wy multiply elements
14p+8=0
We move all terms containing p to the left, all other terms to the right
14p=-8
p=-8/14
p=-4/7
| -17=19n=-150 | | 17=-3(23-m)+2(m-2) | | -2+m/9=-3 | | 6i-3=-18+i | | p+7/3=7 | | -8x-18=-274 | | 47=31-4(x-2) | | p+6/3=3 | | 16x+19=595 | | x-5/6=-1/6 | | n=9/10=-4 | | p–5=-2 | | 22=2h+10 | | -4.5+3=2-8.5x | | B.2/3b-1/3b=4/3 | | 39=26-b | | 7l-4=2l+16 | | -66=-3(m+5) | | 15=-5t^2+20t+1 | | 4(-x+2)=x-5+3 | | 5b+5=14+2b | | -3/7h=42 | | 5(2t-3)-7.5t=0.5(12-0) | | x=8,2x-10 | | -9(-6+b)=135 | | 30-n=59 | | -10(n+1)=60 | | 296-3x=444-5x | | -8=-29-n | | 14=g+5 | | 24=g+5 | | 21/27=x/8 |